The documentary collections of Argentine anarchism - Domínguez Rubio, Lucas (Revista General de Información y Documentación, 2017)
This article analyses the formation of the available documentary collections of Argentine anarchism. Firstly, this work stresses the importance of taking into account the ways in which these archives have been created, in order to situate the documents within the historical research. Secondly, this article describes the different documentary repositories situated in several anarchist institutions and its librarian practices. On the one hand, this allow us to map the available repositories. On the other hand, the description conveyed in this article can be useful in order to start thinking about the specific librarian characteristics of the institutions aligned with political left thought.